Modulatory Effects of a Novel Cyclized Peptide in Reducing the Expression of Markers Linked to Alzheimer's Disease - Brai, Emanuele; Simon, Florian; Cogoni, Antonella; Greenfield, Susan A. (Frontiers in Neuroscience, 2018)
Despite many studies attempt to identify the primary mechanisms underlying neurodegeneration in Alzheimer’s disease (AD), the key events still remain elusive. We have previously shown that a peptide cleaved from the acetylcholinesterase (AChE) C-terminus (T14) can play a pivotal role as a signaling molecule in neurodegeneration, via its interaction with the α7 nicotinic acetylcholine receptor. In this study we aim to determine whether a cyclized variant (NBP14) can antagonize the effects of its linear toxic counterpart, T14, in modulating well-known markers linked to neurodegeneration. We investigate this hypothesis applying NBP14 on ex-vivo rat brain slices containing the basal forebrain. The main goal of this study is to determine, using ex-vivo rat brain slices containing the basal forebrain, whether a cyclized variant (NBP14) of the toxic AChE-derived peptide can antagonize the effects triggered by the linear fragment in modulating well-known markers linked to neurodegeneration. Western blot analysis revealed an inhibitory action of NBP14 on naturally occurring T14 peptide, as well as on endogenous amyloid beta, whereas the expression of the nicotinic receptor and phosphorylated Tau was relatively unaffected. These results further confirm the neurotoxic properties of the AChE-peptide and show for the first time in an ex-vivo preparation the apparent neuroprotective activity of NBP14, over a protracted period of hours, indicating that T14 pathway may offer a new prospect for therapeutic intervention in AD pathobiology.